Menjaga Kontinuitas pada Saat Pengambilan Gambar dalam Media Film - Johanes Baptista Permadi (Bina Nusantara University, 2010)
Film media is a new media to communicate. However, the communication way in this movie is different from other media communication visual. Continuity is a crucial element in communicating through visual media, and sometimes continuity in a film is parted in a scene. The cause of losing continuity needs to be observed more, so there will be a method to anticipate losing continuity of a film in pre-production stage or in preparation stage before actual shooting. The data gained from students’ assignments in ‘Cinematography for Animation’ subject, which close to problem formulation. After the data is gained and compared, there will be experiment using simulation towards application software 3D to find alternative about continuity. The result covers the shooting way to keep continuity and a brave preparation in pre-production stage or before shooting.